Making waves: Time for chemical surface water quality monitoring to catch up with its technical potential - Arndt, Julia; Kirchner, Julia S.; Jewell, Kevin S.; Schluesener, Michael P.; Wick, Arne; Ternes, Thomas A.; Duester, Lars (Water research (Oxford), 2022)
•Today, the monitoring does not fully meet the environmental and societal demands.•Chemical surface water monitoring must better exploit industry 4.0 innovations.•If science, industry and authorities work together, timely monitoring is achievable. A comprehensive real-time evaluation of the chemical status of surface water bodies is still utopian, but in our opinion, it is time to use the momentum delivered by recent advanced technical, infrastructural, and societal developments to get significantly closer. Procedures like inline and online analysis (in situ or in a bypass) with close to real-time analysis and data provision are already available in several industrial sectors. In contrast, atline and offline analysis involving manual sampling and time-decoupled analysis in the laboratory is still common practice in aqueous environmental monitoring. Automated tools for data analysis, verification, and evaluation are changing significantly, becoming more powerful with increasing degrees of automation and the introduction of self-learning systems. In addition, the amount of available data will most likely in near future be increased by societal awareness for water quality and by citizen science. In this analysis, we highlight the significant potential of surface water monitoring techniques, showcase “lighthouse” projects from different sectors, and pin-point gaps we must overcome to strike a path to the future of chemical monitoring of inland surface waters. [Display omitted]